If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8-4c=3(c-2)
We move all terms to the left:
8-4c-(3(c-2))=0
We calculate terms in parentheses: -(3(c-2)), so:We get rid of parentheses
3(c-2)
We multiply parentheses
3c-6
Back to the equation:
-(3c-6)
-4c-3c+6+8=0
We add all the numbers together, and all the variables
-7c+14=0
We move all terms containing c to the left, all other terms to the right
-7c=-14
c=-14/-7
c=+2
| x-46=-96 | | x^-36=8 | | v–v+4v=8 | | 2(x-9)=4x+4 | | 1^3x=12 | | 15+x=5x-x | | 8u+9=6u–9 | | 7=x53 | | x+1/8=8 | | 4+3x=2x-3 | | R=0.75s | | 4+3x=2x–3 | | y-8/y+5=1/6 | | 3x+10=-(×-17) | | 9-25x平方=0 | | 2x4=x | | a+1=7a | | X-7/8+x+7/6=0 | | X+4+x+9=11 | | 3x+4-2=4+7-x | | 2/1/2x-3/4(2x+5)=3/8 | | -90=2(8v+3) | | z-4/z+8=4/7 | | 6+10x=12+45x | | 1=(3+p)/14 | | 12x^2+14x-2=0 | | 2=56-6y | | 64=5x-24+3x | | 0=12x^2+14x-2 | | 36x4-85x2+49=0 | | 3(2r-1)=9(2r-5 | | 2(2x-3)+6x25=0 |